Strategi Public Relations Dalam Membangun Brand Awareness Pada PT. Finfolk Media Nusantara - Feryanda, Jonathan Octa; Wijaya, Lina Sinatra (Jurnal Pustaka Komunikasi, 2024)
People today have begun to switch from conventional media to online media in obtaining information. Because of this transition, many media have emerged and are only engaged in the online field using social media platforms such as Instagram, TikTok, and Youtube. One of these media is PT Finfolk Media Nusantara. In the midst of intense competition between these media, of course, the media needs brand awareness from the public in order to become a trusted media. This research aims to find out the communication strategy owned by PT Finfolk Media Nusantara in building public brand awareness of the company. This research is included in the type of descriptive qualitative research. The data collection techniques used are interviews, observation and documentation. The results showed that PT. Finfolk Media Nusantara planned first before carrying out its communication strategy which was carried out in several stages. In addition, the level of brand awareness of PT. Finfolk Media Nusantara is at the brand recognition level because most have known the company through the content created where the content includes the PT. Finfolk Media Nusantara logo.